Educational Games: Enhancing Father-Child Attachment in Supporting Children's Self-Disclosure and Academic Achievement - Setriani; Meilia Ishar; Daffa Tiara Kurnia Prastiwi (Psyche 165 Journal, 2025)
This study aims to examine the effectiveness of the educational game "Zona Nyaman" in improving father-child attachment, self-disclosure, and academic achievement in elementary school children. Strems from the low involvement of fathers in parenting in Indonesia, which has implications for weak emotional relationships between children and their fathers and reduced support for psychosocial and academic development. The study employed a quasi-experimental design with a pretest-posttest control group approach. The subjects were 30 elementary school students in grade third and fourth, along with their fathers. The experimental group received the "Zona Nyaman" educational game intervention for four sessions, while the control group did not receive the same treatment. The results showed a significant improvement in the experimental group compared to the control in three main variables: father-child attachment, self-disclosure, and academic achievement (p < 0.05). The educational game intervention was proven to strengthen emotional bonds, promote open communication, and enhance children's learning achievement. Father involvement through the medium of educational games not only provides psychological benefits but also supports academic success. Practically, educational games can be integrated into parenting programs and education policies as a strategy to strengthen the role of fathers in child care and learning. Keywords: cooperative play, father-child attachment, self-disclosure, educational games, academic achievement.